Noninvasive optical monitoring of cerebral hemodynamics in a preclinical model of neonatal intraventricular hemorrhage - Jethe, Jyoti V.; Shen, YuBing Y.; La Gamma, Edmund F.; Vinukonda, Govindaiah; Fisher, Jonathan A. N. (Frontiers in Pediatrics, 2025)
Intraventricular hemorrhage (IVH) is a common complication in premature infants and is associated with white matter injury and long-term neurodevelopmental disabilities. Standard diagnostic tools such as cranial ultrasound and MRI are widely used in both preclinical drug development and clinical practice to detect IVH. However, these methods are limited to endpoint assessments of blood accumulation and do not capture real-time changes in germinal matrix blood flow leading to IVH. This limitation could potentially result in missed opportunities to advance drug candidates that may have protective effects against IVH. In this pilot study, we aimed to develop a noninvasive optical approach using diffuse correlation spectroscopy (DCS) to monitor real-time hemodynamic changes associated with hemorrhagic events and pre-hemorrhagic blood flow in a preclinical rabbit model of IVH. DCS measurements were conducted during the experimental induction of IVH, and results were compared with ultrasound and histological analysis to validate findings. Significant changes in hemodynamics were detected in all animals subjected to IVH-inducing procedures, including those that did not show clear positive results on ultrasound 18 h later. The study revealed progressively elevated coefficients of variation in blood flow, largely driven by temporal fluctuations in the <0.25 Hz range. Our findings suggest that real-time optical monitoring with DCS can provide critical insights heralding pathological blood flow changes, offering a more sensitive and informative tool for evaluating potential therapeutics that may help avert the progression to IVH.